2014
DOI: 10.1007/s00299-014-1684-6
|View full text |Cite
|
Sign up to set email alerts
|

The Brachypodium distachyon BdWRKY36 gene confers tolerance to drought stress in transgenic tobacco plants

Abstract: The expression of BdWRKY36 was upregulated by drought treatment. BdWRKY36 -overexpressing transgenic tobacco increased drought tolerance by controlling ROS homeostasis and regulating transcription of stress related genes. WRKY transcription factor plays important roles in plant growth, development and stress response. However, the function of group IIe WRKYs is less known. In this study, we cloned and characterized a gene of group IIe WRKY, designated as BdWRKY36, from Brachypodium distachyon. Transient expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(51 citation statements)
references
References 58 publications
6
45
0
Order By: Relevance
“…Results showed that BdCBF1 was up-regulated rapidly after cold treatment, while BdCBF2 showed an obviously increased expression under salt and drought stresses, which was consistent with previous studies on BdCBF gene functional characterization [73]. BdWRKY36 expression was up-regulated by cold and drought stresses, similar results were reported in previous paper [74]. APXs were the key enzymes in a major hydrogen peroxide-detoxifying system in plant, which was also called ascorbate-glutathione cycle [75].…”
Section: Resultssupporting
confidence: 92%
“…Results showed that BdCBF1 was up-regulated rapidly after cold treatment, while BdCBF2 showed an obviously increased expression under salt and drought stresses, which was consistent with previous studies on BdCBF gene functional characterization [73]. BdWRKY36 expression was up-regulated by cold and drought stresses, similar results were reported in previous paper [74]. APXs were the key enzymes in a major hydrogen peroxide-detoxifying system in plant, which was also called ascorbate-glutathione cycle [75].…”
Section: Resultssupporting
confidence: 92%
“…These results above suggest that overexpression of MbWRKY2 in transgenic tobaccos results in the higher levels of ROSscavenging genes/enzymes. The results above were similar to the overexpression of BdWRKY36 in tobaccos (Sun et al 2015). Furthermore, the expression levels of AtRD29A and AtNCED3 were regarded as indicators for drought stress, which were more higher in VlWRKY48-overexpressing Arabidopsis than WT line when dealt with drought stress (Zhao et al 2018).…”
Section: Discussionsupporting
confidence: 69%
“…Some other WRKY TFs were reported to localize also in the nucleus (Ramamoorthy et al 2008;Liu et al 2014;Wang et al 2016). The chlorophyl content and RWC were usually used as the markers for drought stress degree, which in BdWRKY36-overexpressing tobaccos were more higher than those in WT line under drought stress (Sun et al 2015). Proline, which has been associated with the general stress response, may also be cryoprotective, since proline overproducers display an enhanced drought tolerance (Toka et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The WRKY TFs show high binding affinity to the W-box sequence (T/C)TGAC(C/T) (Rushton et al, 2010). The WRKY TFs are known to play critical roles in biotic and abiotic stress responses, such as pathogen infection (Liu et al, 2005;Mao et al, 2011;Chen et al, 2013;Dey et al, 2014), high salt (Niu et al, 2012;Liang et al, 2017), drought stress (Luo et al, 2013;Sun et al, 2015;Li et al, 2017), oxidative stress , nutrient stress (Chen et al, 2009;Su et al, 2015;Dai et al, 2016) and high temperature (Cai et al, 2015;He et al, 2016). In addition to their important role in stress responses, WRKYs are also involved in a wide range of plant growth and development processes, such as seed dormancy and germination (Luo et al, 2005;Zhang et al, 2011;Ding et al, 2014), seed size (Gu et al, 2017), fruit maturation (Cheng et al, 2016;Ye et al, 2017) and senescence (Besseau et al, 2012;Meng et al, 2013).…”
Section: Introductionmentioning
confidence: 99%